Preparation And Characterization Of A Phytomedicated Antifungal Cream Containing Ocimum Sanctum - Kankaria, Neha; Gupta, M. K.; Nama , Nitin; Vyas, Girish Kumar (Journal of Neonatal Surgery, 2025)
Introduction: Ocimum sanctum (Tulsi) is widely recognized for its diverse pharmacological properties, including antimicrobial and wound healing activities. Objectives: This study aimed to formulate and evaluate an herbal ointment using Ocimum sanctum leaf extracts for potential wound healing applications. The objectives included phytochemical screening, antimicrobial efficacy assessment, and ointment formulation evaluation. Materials and Methods: Leaves of Ocimum sanctum were collected, dried, and subjected to extraction using ethanol. Preliminary phytochemical tests identified the presence of flavonoids, tannins, and phenolics. Antimicrobial activity was assessed using the agar well diffusion method against common wound pathogens. The extract was incorporated into an ointment base, and the formulation was evaluated for physical parameters, stability, and antimicrobial effectiveness. Results: Results demonstrated significant inhibition zones against Staphylococcus aureus and Pseudomonas aeruginosa, confirming potent antimicrobial action. The ointment exhibited good spreadability, homogeneity, and physical stability over 30 days. Conclusion: This study concludes that Ocimum sanctum leaf extract ointment holds promise as an effective herbal wound healing agent with antimicrobial properties. Further clinical studies are warranted to validate its therapeutic potential.